Transnational at Home: Intercultural Gardens and the Social Sustainability of Cities in Innsbruck, Austria - Schermer, Markus (Hábitat y Sociedad, 2014)
The impact of social stability and cohesion on the sustainability of cities gains importance as changing relations between societal groups of different cultural background increasingly shape life in urban environments due to global migration. Urban gardening initiatives and intercultural gardens are receiving growing public attention, especially within Germany and Austria, as a means of migrant integration. The paper uses the intercultural community garden in the Austrian city of Innsbruck as a case to illustrate these processes. The empirical material is based on interviews, besides observations during a public garden visit and newspaper clippings. The paper describes changing patterns from classical emigration over work migration to transmigration and living in transnational social spaces. Intercultural gardens are conceptualized as specific forms of transnational spaces, which localize them and at the same time open them to multi-ethnic spaces. As intercultural gardens are organized as communal spaces, they provide new social networks for persons from different provenance and encourage various learning processes. Thus they impact on two key dimensions of the social sustainability of cities, social cohesion and the stability of communities, and allow new ways of interaction between different cultures beyond assimilation and integration.